Electrochemical Evaluation of Strontium-Doped Micro-Arc Oxidation Surfaces on Titanium - Alexandra C. Alves; Carolina Durães; Fatih Toptan (Metals)
Titanium (Ti) alloys are widely used in biomedical applications but face challenges like poor biological activity and corrosion at modular interfaces. Strontium (Sr)-doped micro-arc oxidation (MAO) surfaces are proposed to improve biocompatibility and tribocorrosion resistance. This study examines the electrochemical behaviour of Ti surfaces treated with 0.0013 M and 0.13 M Sr-doped MAO via open circuit potential, potentiodynamic polarisation, and electrochemical impedance spectroscopy in a basic physiological solution at 37 °C. The results indicate that higher Sr concentrations led to lower passivation current densities (more than two times lower than at the lowest Sr concentration) and reduced barrier layer capacitance (more than one and a half times lower than at the lowest Sr concentration), suggesting improved corrosion resistance for Sr-enriched MAO treatments on Ti implants.